HABITAT TEMPAT BERTELUR PENYU HIJAU (Chelonia mydas) DI KAWASAN TAMAN WISATA ALAM SUNGAI LIKU KABUPATEN SAMBAS KALIMANTAN BARAT - Pradana, Ferry Akasa; Said, Syafruddin; Siahaan, Sarma (Universitas Tanjungpura, 2013)
The research objective is to examine the characteristics of green turtle nesting site habitat, the research methods used were observation by conducting direct observation of the object of study in which the data collection phase by measuring the length of the beach, beach slope, distance nest, the highest tide, low tide lowest, air temperature and humidity and vegetation as well as the identification of turtles were found at the time of the study. Species of sea turtle nesting activity on this beach is Chelonia mydas (green turtle). Based on the results of research in the area of ??the River TWA Twists obtained long beach 9893; slope of the beach 6%; distance of 8-22 meters nest; highest tide 8-17 meters; lowest ebb 21-32 meters; highest with a mean air temperature 30 ? C and 26 lows ,4?C; humidity with the highest rates at 69.7% and the lowest 73%; Casuarinaceae equisetifolia dominated vegetation (spruce) and turtles were found at the time of the study was 4 Chelonia mydas (green turtle) and 2 turtles Eretmochelys imbricate (hawksbill turtle). Key words: spawning habitat, physical characteristics, identification of turtles.